Water Monitor Lizard (𝙑𝙖𝙧𝙖𝙣𝙪𝙨 𝙨𝙖𝙡𝙫𝙖𝙩𝙤𝙧 𝙢𝙖𝙘𝙧𝙤𝙢𝙖𝙘𝙪𝙡𝙖𝙩𝙪𝙨) distribution in Phitsanulok Province - Tanasarpaiboon, Supatcharee (Burapha Science Journal, 2026)
Background and Objectives : Urbanization may have positive or negative effects on presence and distribution of wildlife. The water monitor lizard (Varanus salvator macromaculatus) is a reptile that inhabits wide range of habitats, such as urban areas, swamp or wetland, but few occurrences in some area, such as forests. This study was aimed to examine the factors that influence the distribution of water monitor lizards in Phitsanulok province because of the area comprising of various habitat types. Methodology : The surveys in districts in Phitsanulok province and secondary data from people and iNaturalist were collected. The species distribution model were analyzed in the software Maxent based on environmental variables, including elevation above sea level (m.), distance from road (m), distance to water resources (m), landuse types (i.e., agriculture , wetland, forest, water, urban, and miscellaneous), and sub-district population density in 2020 to explain the distribution of water monitor lizards in Phitsanulok. The model were evaluated using ROC and AUC. The contribution of each environmental variable to the lizard occurrence was explained using the Jacknife Test. Main Results : There were 42 occurrences of the water monitor lizards during February 2020 to February 2021. The distribution model outputs using Maxent based on occurrences and environmental variables showed that the model have AUC = 0.933, which suggested that the data can excellently explain the distribution of the water monitor lizard. The landuse and the elevation made the most contribution to the occurrence of the lizard, which accounting for 60.5% and 26.6%, respectively. Conclusions : Occurrence of the water monitor lizard in Phitsanulok province were not many as the survey were conducted in short time periods and not regularly. However, they were usually found in urban areas with human habitation and low land.